Editorial Notes: Communication, Media And Its Impact In Times Of Crisis - Rosninawati Hussin; Osama Kanaker (USIM Press, 2024)
Vol. 1 No. 2 (2021): Al-I'lam: Journal of Contemporary Islamic Communication and Media